2018
DOI: 10.26444/aaem/78787
|View full text |Cite
|
Sign up to set email alerts
|

Sweat iron concentration during 4-week exercise training

Abstract: Introduction. One possible way of iron loss is sweating. It is unclear how physical activity performed by untrained individuals affects the iron status in sweat. Objective. The purpose of this study was to analyse iron concentration in sweat during 4-week exercise training to determine the changes in iron excretion during follow-up exercises. Materials and method. 43 untrained volunteers participated in the study, 29 of whom completed the full exercise programme. The training programme consisted of exercises o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Sweat is an aqueous solution that contains a great variety of compounds, such as NaCl, lactate [1], nitrogenous compounds (ammonia, urea and amino acids [2,3]), metal ions (e.g., zinc and iron [4,5]), heavy metals (e.g., arsenic, cadmium, lead and mercury [6]), immune biomarkers (e.g., IgG, IgD and interleukin-1α [7]), cortisol and stress biomarkers [8], lactoferrin [9] and xenobiotics (e.g., drugs of abuse [10] and ethanol [11,12]). The main function of sweat is thermoregulation, leading to heat dissipation by water evaporation [1] in response to an increase in body core temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Sweat is an aqueous solution that contains a great variety of compounds, such as NaCl, lactate [1], nitrogenous compounds (ammonia, urea and amino acids [2,3]), metal ions (e.g., zinc and iron [4,5]), heavy metals (e.g., arsenic, cadmium, lead and mercury [6]), immune biomarkers (e.g., IgG, IgD and interleukin-1α [7]), cortisol and stress biomarkers [8], lactoferrin [9] and xenobiotics (e.g., drugs of abuse [10] and ethanol [11,12]). The main function of sweat is thermoregulation, leading to heat dissipation by water evaporation [1] in response to an increase in body core temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies related to elemental analysis of sweat by ICP-MS address studies of elimination of bioaccumulated toxic elements, comparing normothermic and hyperthermic conditions, or after physical exercise. 157,158 In other studies, the release of essential elements such as Fe 159 or Mg and P 160 has been investigated. Although a non-metal, a few words must be reserved for the quantification of chloride in sweat of new-borns by ICP-MS to detect cystic fibrosis, the commonest, inherited life-shortening condition of childhood.…”
Section: Applications For Disease Evaluation And/or Diagnosismentioning
confidence: 99%
“…Iron deficiency is frequent among endurance athletes with excessive training regimens [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. The majority of studies have shown an iron deficiency in athletes from a variety of sporting disciplines [ [15] , [16] , [17] , [18] ] that require a high level of fitness to sustain proficient, physical, and cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms that cause iron loss during exercise are hemolysis due to mechanical forces and oxidative stress, gastrointestinal and urinary tract bleeding due to microscopic lesions, and extreme sweating, which can result in iron deficiency [ 13 ]. Sweat excretion from eccrine sweat glands is primarily a mechanism of thermoregulation but is also a way the body loses iron [ 9 , 27 ]. For instance, the daily sweat-related iron loss is estimated to be 1–2 mg per 2 h of exercise, equivalent to 1% and 3% of recommended daily intake of iron for women and men respectively [ 18 , [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation